2017
DOI: 10.1177/014556131709600707
|View full text |Cite
|
Sign up to set email alerts
|

Audiometry Results and TEOAE and DPOAE Amplitudes in Men Taking a Phosphodiesterase Type 5 Inhibitor for Erectile Dysfunction

Abstract: We conducted a prospective study of transient evoked otoacoustic emissions (TEOAEs) and distortion-product otoacoustic emissions (DPOAEs) in men who were taking an oral phosphodiesterase type 5 (PDE5) inhibitor for erectile dysfunction. Our study group was made up of 30 men (60 ears), aged 34 to 60 years (mean: 50.9). They were randomly divided into three groups; 10 men were given sildenafil (Viagra) at 50 mg twice a week, 10 were given tadalafil (Cialis) at 20 mg twice a week, and 10 were given vardenafil (Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Pentoxyifylline, a nonspecific PDE inhibitor, is one of several vasodilators used in the treatment of sudden SNHL (18,243). A recent study demonstrated that patients treated with sildenafil, taldalafil, and vardenafil have improvements in hearing (225), and the results of a small experimental trial indicated that 60% of patients reported substantial reduction or elimination of Ménière's disease symptoms following administration of sildenafil (29). Taken together, therefore, animal and clinical studies indicate that PDE5 inhibitors have complex positive and negative effects on inner ear physiology.…”
Section: Pde Inhibitorsmentioning
confidence: 99%
“…Pentoxyifylline, a nonspecific PDE inhibitor, is one of several vasodilators used in the treatment of sudden SNHL (18,243). A recent study demonstrated that patients treated with sildenafil, taldalafil, and vardenafil have improvements in hearing (225), and the results of a small experimental trial indicated that 60% of patients reported substantial reduction or elimination of Ménière's disease symptoms following administration of sildenafil (29). Taken together, therefore, animal and clinical studies indicate that PDE5 inhibitors have complex positive and negative effects on inner ear physiology.…”
Section: Pde Inhibitorsmentioning
confidence: 99%